A situação da alfabetização dos falantes de línguas de imigração no contexto brasileiro - Horst, Cristiane (Contingentia, 2009)
One of the most striking moments in the life of Brazilian children speaking a minority language happens when they go to elementary school. There, the attitude towards the family language is completely indifferent, if not openly hostile, since the school sees its duty limited to alphabetising the child in the official language, which is Portuguese. This article reflects on practical strategies for teaching school children speaking immigrant languages, focussing on the different meaning of alphabetisation in minority language contexts and on the advantages of early bilingualism, ascertained by research in cognitive science (cf. Bialystok 2005). Immigrant contexts of this nature are being studied in the linguistic atlas project ALMA-H (Atlas Linguístico-Contatual das Minorias Alemãs na Bacia do Prata - Hunsrückisch). Based on data from this project and considering the Brazilian educational context the article proposes strategies that could help to improve the alphabetisation process of those groups by reconciling the dissociation that separates school contexts from family contexts in areas of collective bilingualism in Brazil.